Efficacy and safety of embolization of dural arteriovenous fistulas via the ophthalmic artery. Issue 3 (June 2021) - Mayercik, Vera A; Sussman, Eric S; Pulli, Benjamin; Dodd, Robert L; Do, Huy M; Telischak, Nicholas A; Marks, Michael P; Steinberg, Gary K; Chang, Steven D; Heit, Jeremy J
Introduction: Dural arteriovenous fistulae (DAVF) are vascular lesions with arteriovenous shunting that may be treated with surgical obliteration or endovascular embolization. Some DAVF, such as anterior cranial fossa DAVF (AC-DAVF) derive their arterial supply from ophthalmic artery branches in nearly all cases, and trans-arterial embolization carries a risk of vision loss. We determined the efficacy and safety of trans-ophthalmic artery embolization of DAVF. Materials and methods: We performed a retrospective cohort study of all patients with DAVF treated by trans-ophthalmic artery embolization from 2012 to 2020. Primary outcome was angiographic cure of the DAVF. Secondary outcomes included vision loss, visual impairment, orbital cranial nerve injury, stroke, modified Rankin Scale at 90-days, and mortality. Results: 12 patients met inclusion criteria (9 males; 3 females). 10 patients had AC-DAVF. Patient age was 59.7  ±  9.5 (mean ± SD) years. Patients presented with intracranial hemorrhage (4 patients), headache (4 patients), amaurosis fugax (1 patients), or were incidentally discovered (2 patients). DAVF Cognard grades were: II (1 patient), III (6 patients), and IV (5 patients). DAVF were embolized with Onyx (10 patients), nBCA glue (1 patient), and a combination of coils and Onyx (1 patient). DAVF cure was achieved in 11 patients (92%). No patients experienced vision loss, death, or permanent disability. One patient experienced a minor complication of blurry vision attributed to posterior ischemic optic neuropathy. 90-day mRS was 0 (10 patients) and 1 (2 patients). Conclusions: Trans-ophthalmic artery embolization is an effective and safe treatment for DAVF.